Micronuclei frequency and exposure to chemical mixtures in three Colombian mining populations (2023)
The Colombian mining industry has witnessed significant growth. Depending on the scale and mineral extracted, complex chemical mixtures are generated, impacting the health of occupationally exposed populations and communities near mining projects. Increasing evidence suggests that chromosomal instability (CIN) is an important link between the development of certain diseases and exposure to complex mixtures. To better understand the effects of exposure to complex mixtures we performed a biomonitoring study on 407 healthy individuals from four areas: three located in municipalities exploiting different-scale mining systems and a reference area with no mining activity. Large, medium, and small-scale mining systems were analyzed in Montelibano (Córdoba), artisanal and small-scale mining (ASGM) in Nechí (Antioquia), and a closed mining system in Aranzazu (Caldas). The reference area with no mining activity was established in Montería (Córdoba). ICP-MS measured multi-elemental exposure in hair, and CIN was evaluated using the cytokinesis-block micronucleus technique (MNBN). Exposure to mixtures of chemical elements was comparable in workers and residents of the mining areas but significantly higher compared to reference individuals. In Montelibano, increased MNBN frequencies were associated with combined exposure to Se, Hg, Mn, Pb, and Mg. This distinct pattern significantly differed from other areas. Specifically, in Nechí, Cr, Ni, Hg, Se, and Mg emerged as the primary contributors to elevated frequencies of MNBN. In contrast, a combination of Hg and Ni played a role in increasing MNBN in Aranzazu. Interestingly, Se consistently correlated with increased MNBN frequencies across all active mining areas. Chemical elements in Montelibano exhibit a broader range compared to other mining zones, reflecting the characteristics of the high-impact and large-scale mining in the area. This research provides valuable insights into the effects of exposure to chemical mixtures, underscoring the importance of employing this approach in the risk assessment of communities, especially those from residential areas.